Love in Sir Charles George Douglas Roberts' Selected Poems - Ade, Ari; Rahayu, Anik Cahyaning (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This thesis explores love in five selected poems by Sir Charles George Douglas Roberts: Moonlight, The Fear of Love, Love's Translator, Presence, and The Footpath. The research aims to find the types of love and identify and analyze the figurative language exposing the theme. The intrinsic approach is used for this research. An extrinsic approach, the psychological approach from John Lee’s theory is also used to analyze the types of love because love relates to psychology. The data source used in this research consists of the five poems. A descriptive qualitative method is used in this research. Each poem demonstrates different types of love as defined by John Lee’s theory, including Eros, Mania, and Storge, using figurative language to express deeper emotions and meanings. Moonlight shows Eros love through imagery, metaphors, personification, apostrophe, and hyperbole, capturing intense longing and desire. The Fear of Love shows Mania love, characterized by obsession and anxiety, through imagery, metaphor, and hyperbole. Love's Translator uses symbols of nature and imagery to reflect the physical attraction and emotional depth of Eros love. In Presence, Eros love is shown through imagery, personification, and hyperbole showing how the lover’s presence transforms the speaker's perception of the world. Lately, The Footpath shows Storge love, emphasizing deep friendship and shared memories, with imagery, metaphors, and apostrophe, shows the bond between the speaker and his beloved. In conclusion, this research shows how figurative language is used to portray the kinds of love theme of the five poems.